A2.4 Are protein tyrosine phosphatase-n1 polymorphisms associated with ankylosing spondylitis? – a pilot study. (31st January 2014) - Luísa Cartaxo, Ana; Godet, Inês; Ligeiro, Dário; Matos, Mafalda; Branco, Jaime C; Pimentel-Santos, FM
Abstract : Background and Objectives: Association between ankylosing spondylitis (AS) and PTPN1 (protein tyrosine phosphatase, non-receptor type 1) gene, was recently reported in Portuguese population, in a study of whole blood transcriptional profiling, performed by our group. Protein tyrosine phosphatase 1B (PTP1B) is a ubiquitously expressed enzyme shown to negatively regulate multiple tyrosine phosphorylation-dependent signalling pathways, including IL4 signalling and IL23 pathway (dephosphorylation of JAK2 and TYK2 kinases). In addition, several PTPN1 single nucleotide polymorphisms (SNPs), were significantly associated with coronary calcified plaque in type 2 Diabetes patients. We sought to test the association between SNPs in this gene and susceptibility to AS among a Portuguese population. In addition, we investigated the association of this gene with activity (BASDAI), functional (BASFI), metrological (BASMI) and radiological severity (mSASSS) indexes. Materials and Methods: The study was conducted on 330 AS cases and 225 ethnically matched Portuguese healthy controls. AS was defined according to the modified New York Criteria. Genotyping of PTPN1 variants (rs2206656 and rs932420) was carried out with TaqMan allelic discrimination assays. Association analysis was performed using the Cochrane-Armitage and linear regression tests of genotypes as implemented in PLINK for dichotomous and quantitative variables respectively. Analyses of BASDAI, BASFI, BASMI and mSASSS were stratified for sex and disease duration. Results: Two markers (rs2206656, rs932420) were analysed. None of them showed significant single- locus disease association (p > 0.05) with AS in the Portuguese population. No association was observed between these SNPs and BASDAI, BASFI, BASMI or mSASSS. Conclusions: These results suggest that PTPN1, contrary to recently described for PTPN2, is probably not a major determinant of susceptibility to AS. In Portuguese population, PTPN1 polymorphisms do not markedly influence AS disease activity and severity, as measured by BASDAI, BASFI, BASMI and mSASSS.